Earth-Skimming Ultrahigh Energy Tau Neutrinos Simulated with Monte Carlo Method and CONEX Code - Bouzid Boussaha; Tariq Bitam (Advances in High Energy Physics)
This paper is aimed at studying the feasibility of building an Earth-skimming cosmic tau neutrinos detector, with the aim of eventually identifying the ideal dimensions of a natural site mountain-valley for the detection of very high energy neutrinos tau range from 1016eV to 1020eV, as well as possibly locate one such site in Algeria. First, a Monte Carlo simulation of the neutrino-[mountain] matter interaction as well as the resulting decay of the tau lepton is conducted to determine the optimal dimensions of the mountain as well as the location of the tau decay in the valley. Second, a CORSIKA (COsmic Ray Simulation for KAscade) simulation with the CONEX option is conducted to track the evolution of the almost horizontal air shower initiated by the tau lepton. Many particles are produced, which are part of the shower components: electrons, muons, gammas, pions, etc. The study of the spatial distribution of these particles enables the discovery of the optimal width of the valley, and consequently, the distance at which to lay the detection network.